Produção de etanol 2g através de Opuntia ficus-indica utilizando Saccharomyces cerevisiae e Kluyveromyces marxianus - Barbosa, Kledson Lopes (2015)
Energy demand has grown due to the pressures caused by the emission control of greenhouse gases and due to oil exploration and its derivatives as an energy source. An alternative to reduce emissions of gases that cause the greenhouse effect is mix ethanol in gasoline to oxygenated. The worldwide increase generated by the demand for ethanol requires the search for alternative processes for implementation of ethanol production. An alternative is the fermentation of lignocellulosic biomass to bioethanol production. The degree of complexity involved in the structure and composition of the lignocellulosic biomass; and the availability of sugars present in cellulose and hemicellulose require pre-treatment processes in the production of lignocellulosic ethanol. The steps involved in the conversion of sugars to ethanol are pre-treatment, enzymatic hydrolysis and fermentation of the hydrolyzate. This work shows the results related to fermentability of pre-treated and hydrolyzed biomass Opuntia ficus-indica in order to compare the efficiency of industrial strains of Saccharomyces cerevisiae and Kluyveromyces marxianus for ethanol production. In the methodology, it was employed an experimental design 2³ in order to obtain the best condition by the variables investigated concentration of acid (0.5%, 1.0%) pre-treatment time (30 min, 60 min) and the amount of mass (1g, 2g). The pre-treatment under the condition of 1.0% of sulfuric acid for 30 minutes with 2g of biomass was the best result, being the chosen condition to follow the enzymatic hydrolysis and fermentation steps. Ethanol production in the fermentation was 5.85 g L-1 with S. cerevisiae, 5.15 g L-1 at K.marxinus and 5.74 g L-1 with the process conducted with the two species. The consumption of reducing sugars during the fermentation stage were similar for the three fermentation conditions.